Alih Fungsi Hutan untuk Industri Sawit dan Pertambangan: Analisis Fiqh Siyasah terhadap Legalitas Keputusan Ūlī al-amr dalam Perspektif Maqāṣid al-Syarī‘ah - Mohammad Robi al Muhasibi (Syariah: Journal of Fiqh Studies, 2026)
This study examines the legality of forest conversion policies into palm oil and mining industrial areas from the perspective of Islamic jurisprudence and maqāṣid al-sharī‘ah. The research employs a qualitative library research approach using a normative-uṣūlī method combined with empirical analysis of deforestation, agrarian conflicts, and ecological degradation in Indonesia. Primary sources include classical works such as Al-Muwāfaqāt by al-Shāṭibī, Al-Mustaṣfā by al-Ghazālī, Al-Asybāh wa al-Naẓā’ir by al-Suyūṭī, and Al-Aḥkām al-Sulṭāniyyah by al-Māwardī. The analysis applies the method of taḥqīq al-manāṭ to assess the conformity between legal maxims, the concept of maṣlaḥah-mafsadah, and empirical realities. The findings indicate that administrative legality does not automatically establish shar‘ī legitimacy when state policies generate substantial ecological and social harm. Empirical data demonstrate that palm oil and mining expansion contribute to deforestation, agrarian disputes, ecosystem degradation, and threats to social sustainability. Within the framework of maqāṣid al-sharī‘ah, these impacts endanger ḥifẓ al-nafs, ḥifẓ al-nasl, ḥifẓ al-māl, and the contemporary development of ḥifẓ al-bi’ah. The study concludes that the authority of ūlī al-amr is conditional and must remain subject to the principle of taṣarruf al-imām manūṭun bi al-maṣlaḥah. Therefore, industrial policies should be reconstructed toward sustainable green industry models that balance economic development with ecological protection and public welfare. Keywords: environmental fiqh, ulil amri, forest conversion, maqāṣid al-sharī‘ah, public welfare.